SCIENCE CLUB OF PURWOKERTO SEBAGAI SARANA MENINGKATKAN POLA PIKIR ILMIAH PELAJAR PURWOKERTO - Mukti, Muhammad Dwiyan; Maulana, Rizki Fauzi; Wulandari, Rani; Qonita, Nael Huda (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Nowadays, the existence of juvenile delinquency in Junior high level or even Senior high is uncontrollable. Whether itâs brawl or even another way of naughtiness. they donât realize that its can destruct their future. Juvenile delinquency happens because there is no right place to express their creativity. Science Club (KIR), is a extracurricular that exist in senior high level. This extracurricular is focus on science, whether its exact or even social science. Science Club (KIR) in Regional level is very needed because it can be right place for teenager to interact with another student from different school and also minimalize juvenile delinquency.